Indonesian Higher Education Marketing: Barrier and Challenges in New Normal Education and its Impact to Competitive Advantages - Purnomo Purnomo; Chairul Furqon; Disman Disman; Ratih Hurriyati (Budapest International Research and Critics University, 2022)
In the context of the COVID-19 pandemic, the government, parents, and students themselves have different perceptions of learning needs. In Indonesia, there are three policies issued by the Ministry of Education and Culture related to the implementation of higher education in the era of adaptation to new habits (New Normal), related to the implementation of the new academic year, the implementation of the learning process, and the use of campus facilities or services. In the era of the Covid-19 Pandemic, students are forced to access sources of knowledge and information in cyberspace and can be accessed anywhere. The transition from offline to online teaching and learning can be complex, problematic and requires an evolutionary (gradual) effort. Substantial realistic efforts are needed to transform from a face-to-face teaching culture. especially in terms of offering higher education to prospective students, there are many challenges and obstacles that are passed in the higher education marketing process, in this study it is examined how higher education offers should be made during a pandemic, what are the challenges and obstacles and its impact to higher education competitive advantages, through a quantitative approach and data run by PLS-SEM. The result of this study shown education marketing with ideal STP affect Higher Education Competitiveness and recomend that education marketers must be able to distinguish their market between the short-term market, future market and primary market, secondary market in targeting consumers. A short-term target market is a market that’s more suitable for the pandemic term which generates sales in the near future.